2021
DOI: 10.1186/s12884-021-03901-7
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene during facility-based childbirth in Cambodia: a theory-driven, mixed-methods observational study

Abstract: Background Despite current efforts to improve hand hygiene in health care facilities, compliance among birth attendants remains low. Current improvement strategies are inadequate, largely focusing on a limited set of known behavioural determinants or addressing hand hygiene as part of a generalized set of hygiene behaviours. To inform the design of a facility –based hand hygiene behaviour change intervention in Kampong Chhnang, Cambodia, a theory-driven formative research study was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Infrastructure alone will not address the risk of infection to mothers and newborns; good hygiene practices are also necessary. Even when the necessary infrastructure is in place, hand hygiene can be limited during labour and delivery (Nalule et al 2021).…”
Section: Wash In All Settingsmentioning
confidence: 99%
“…Infrastructure alone will not address the risk of infection to mothers and newborns; good hygiene practices are also necessary. Even when the necessary infrastructure is in place, hand hygiene can be limited during labour and delivery (Nalule et al 2021).…”
Section: Wash In All Settingsmentioning
confidence: 99%
“…A systematic review conducted in 2014 found a significant association between poor WASH practice and maternal mortality (Benova, et al, 2014). Furthermore, the historical link between hygiene and childbirth and the effect of clean water accessibility on safe delivery is well recognized (Semmelweis and Semmelweis, 1983;Gould, 2010;Nalule, Y. et al, 2021). Therefore, improved WASH is crucial to promote health and sustainable development, as evidenced by the studies described above.…”
Section: Introductionmentioning
confidence: 99%
“…Hygiene interventions spanning both healthcare facility (HCF) and home environments are scarce with limited evidence around their effectiveness at changing handwashing behaviour 11 , 24 . Hand hygiene studies to-date mostly focus on individual care periods, particularly birth 13 , 17 , 18 , 25 27 or the late post-natal period (> 7 days of life) 8 , 20 , 21 , 28 . Postnatal care in the critical days following facility-based birth remains under investigated 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this intervention, caregivers included midwives during childbirth, midwives, mothers, and non-maternal caregivers during post-natal care of the new-born, and mothers and other non-maternal caregivers in the home environment. Formative work in this setting documented low hand hygiene compliance in both the facilities and in the home and identified various psychosocial, physical and contextual factors influencing these practices 18 , 19 . Despite availability of functioning hand hygiene infrastructure and materials and demonstrated understanding of infection risk due to inadequate hand hygiene, barriers to effective hand hygiene adherence from midwives included limited understanding of hand or glove recontamination risk, habits and norms around inappropriate gloving practices, perceived lack of time from high workloads and low staffing, and low perception of newborn infection risk 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation